Digital human rights and perspectives of their inclusion in the legislation - Ablameyko, Maria S.; Shakel, Nadzeya V. (Journal of the Belarusian State University. Law, 2022)
The approaches to the protection of human rights in the context of digitalisation are analysed. The positions of scientists researching various aspects of the realisation of human rights in the digital environment are evaluated. Special attention is paid to the study of the right of access to information, which is being transformed in digital conditions, allowing the realisation of the rights to access the Internet, to receive online services and information within digital services, etc. It is proposed to implement digital human rights in the activities of smart cities. Specific proposals on the legislative regulation of digital rights in the Republic of Belarus are given.